MENUMBUHKAN KREATIFITAS MELALUI PEMBERIAN KETERAMPILAN SELAMA MENUNGGU MASA PANEN KARET - Basuki Basuki; Rahmi Widyanti; Khuzaini Khuzaini (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2024)
Community empowerment must be carried out continuously considering that changes occur all the time. Changes can be caused by government policies, economic conditions or changes in natural conditions. This has an impact on people's life patterns and follows these changes.        This training activity to foster creativity aims to help and provide assistance to rubber farming communities in overcoming economic disparities while waiting for the harvest period. This activity can encourage the emergence of creative thoughts/ideas to produce other products so that you can earn your own income without expecting continuous government assistance. It is hoped that this training can increase rubber farmers' innovation with their own capital.       The problem faced by rubber farmers is that they do not have the skills to fulfill their daily needs and while they wait for the harvest period. Therefore, the environment demands creativity and innovation with one's own capital. Through this training, it can open the thinking horizons of farming communities in opening up business opportunities with relatively small capital.  Keywords: Creativities, harvest period, self capital